Where there is danger - Jurgenson, Luba, 1958- (Jews of Russia and Eastern Europe and their legacy, 2019)
"Writer, professor, translator and editor Luba Jurgenson lives between two languages--her native Russian and her adopted French. She recounts the coexistence of these two languages, as well as two bodies and two worlds, in an autobiographical text packed with fascinating anecdotes. Living bilingually can be uncomfortable, but this strange in-between state can equally serve as a refuge and inspire creativity. Jurgenson sheds light on this little-explored territory with lively prose and a keen awareness of her historical and literary context. Language, identity, translation, and the self: all are intertwined. The ceaseless journey of bilingualism is at last revealed"--Provided by publisher.